Research on the Influence of Media Internalized Pressure on College Students’ Sports Participation—Chained Intermediary Analysis of Social Physique Anxiety and Weight Control Self-Efficacy - Ouyang, Yiyi; Luo, Jiong; Teng, Jinsheng; Zhang, Tingran; Wang, Kun; Li, Jing (Frontiers in Psychology, 2021)
Purpose: Discuss the relationship among college students’ media internalized pressure, social physique anxiety, weight control self-efficacy, and sports participation in providing a reference for promoting college students to develop healthy and confident living habits. Methods: Take Southwest University in China as the object, select the subjects by stratified random sampling, and process the data with SPSS19.0 and AMOS21.0 statistical software. Results: (1) Media internalized pressure is positively correlated with social physique anxiety, weight control self-efficacy, and sports participation; social physique anxiety is significantly positively correlated with weight control self-efficacy and sports participation, and weight control self-efficacy is significantly positively correlated with sports participation; (2) media internalized pressure has a direct effect on sports participation (ES = 0.456), and social physique anxiety (ES = 0.136) and weight control self-efficacy (ES = 0.102) play significant mediating roles in the relationship between media internalized pressure and sports participation, respectively; the chained mediating force of social physique anxiety and weight control self-efficacy also reaches a significant level (ES = 0.027). Conclusion: Media internalized pressure can influence college students’ sports participation through the direct path as well as indirect paths such as social physique anxiety, the intermediary effect of weight control self-efficacy, and chained intermediary effect of social physique anxiety–weight control self-efficacy, and social physique anxiety is another key factor affecting college students’ sports participation except media internalized pressure.